Over-expression of two putative disease resistant genes NBS-type rgc and wrky against Fusarium oxysporum f. sp. cubense in plants / Siti Nur Akmar Mazlin - Siti Nur Akmar , Mazlin (2018)
The widespread global distribution of Fusarium wilt disease caused by Fusarium oxysporum f. sp. cubense (Foc) has affected the production of banana fruits in almost all edible banana cultivars. This is due to lack of disease resistance banana, parthenocarpic nature of bananas and sterile fruits. This has limited the conventional breeding program to develop Fusarium wilt-resistant line. Strategies to control the Fusarium wilt disease are also ineffective due to polycyclic nature of the disease. Therefore, development of Fusarium-resistant banana through genetic engineering is of significant importance. In the past, two candidate genes, namely nucleotide binding site (NBS) type of resistance gene candidate (RGC) and WRKY transcription factor, showed up-regulation expression during Foc infection in banana. Therefore, in this study, NBS-type RGC and WRKY isolated from banana were molecularly characterized and expressed in banana and tobacco, respectively. NBS-type RGC was successfully isolated from Musa acuminata ssp. malaccensis (MAN-RF) with cDNA length of 1,160 bp and cloned. The constructed binary vector pCAMBIA1304-MAN-RF was transformed into embryogenic cells of Musa acuminata cv. ‘Berangan’ and leaf disc of tobacco, Nicotiana tabacum L. cv. SR1 via Agrobacterium-mediated transformation. The PCR analysis of the putative transgenic of Musa acuminata cv. ‘Berangan’ plantlets confirmed the stable integration into the genome. The transcript levels of MAN-RF were determined using 2-ΔΔCt method in transgenic lines of T7, T13 and T14 resulted in 2.47, 3.29 and 4.69-fold changes compared to the untransformed plant, respectively. Unfortunately, the transformation of tobacco was unsuccessful. Therefore, the expression analysis of MAN-RF in tobacco was unable to perform. While in WRKY transcription factor study, full-length WRKY gDNA and cDNA were successfully isolated from Musa acuminata ssp. malaccensis (MamWRKY) by using ‘rapid amplification of cDNA ends’ (RACE) with 1,414 bp and 1,224 bp length, respectively. The full-length MamWRKY cDNA contains 861 bp of coding sequences (CDS), which encodes 286 amino acids with the structural features of group IIe in the WRKY proteins family and predicted to have a molecular mass of 30.16 kDa and a theoretical pI of 5.05. The constructed binary vector pCAMBIA1304-MamWRKY CDS was introduced into leaf disc Nicotiana tabacum L. cv. SR1 via Agrobacterium-mediated transformation. The transcript levels were determined using 2-ΔΔCt method in transgenic lines of W1, W2 and W4 resulted in 809.002, 739.804 and 1153.659-fold changes compared to the untransformed plant, respectively. A functional study of MamWRKY was carried out in tobacco with PR1a as our reference gene. PR1a is one of a pathogen-responsive gene, which salicylic acid-inducible defense gene of tobacco. The elevated expression of PR1a in transgenic lines, W1, W2 and W4 was at 968.763, 23.984 and 6812.648-fold changes, respectively, higher than untransformed plants. This finding suggests that MamWKRY might function as a transcriptional regulator upstream of defense signaling pathways. This study has laid the foundation for further study the role of NBS-type RGC and MamWRKY in the plant’s defense mechanism as the candidate genes that might facilitate banana improvement programs.